1980
DOI: 10.1111/j.1471-0528.1980.tb04445.x
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effect of Abdominal Hysterectomy on Intravesical Pressure and Detrusor Activity

Abstract: This study was undertaken to determine the effect of simple abdominal hysterectomy on bladder function in the first postoperative week. It was found that initially there was a significant reduction in voluntary capacity, a rise in residual volume and an increase in intravesical pressure but that this was returning to normal after one week. The degree to which these changes occurred did not seem to be related to postoperative disturbances of micturition. DIFFICULTY in establishing normal micturition after pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 2 publications
3
10
0
1
Order By: Relevance
“…Current theories concerning the etiology of transient postoperative urinary retention include the effects of periurethral and perivesical edema [Seski and Diokno, 1977;Wake, 1980], inhibition of detrusor contractility [Seski and Diokno, 1977], failure of the external urethral sphincter to relax [Tammela et al, 1986a;Petros et al, 1993;Kaplan et al, 1997Gonullu et al, 1999, and outlet obstruction due to bladder neck elevation after surgery for stress urinary incontinence [Zimmern et al, 1987;Webster and Kreder, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Current theories concerning the etiology of transient postoperative urinary retention include the effects of periurethral and perivesical edema [Seski and Diokno, 1977;Wake, 1980], inhibition of detrusor contractility [Seski and Diokno, 1977], failure of the external urethral sphincter to relax [Tammela et al, 1986a;Petros et al, 1993;Kaplan et al, 1997Gonullu et al, 1999, and outlet obstruction due to bladder neck elevation after surgery for stress urinary incontinence [Zimmern et al, 1987;Webster and Kreder, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…[15] However, evidence neither supports avoidance of clinically indicated hysterectomy nor performance of supracervical hysterectomy as measures to prevent urinary incontinence. [2223]…”
Section: Risks For Urinary Incontinencementioning
confidence: 99%
“…The response rate was only 60-67% but no differences were found between these groups with respect to urinary symptoms other than the incidence of stress urinary incontinence, which actually decreased following total abdominal hysterectomy. Wake [35], Vervest et al [41] and Langer et al [39] have all shown a lack of clinically significant urodynamic changes or urinary incontinence following hysterectomy with studies that had each used prospective pre-and postoperative urodynamics. Demirci et al [46] used perineal ultrasound to assess the bladder neck before and one year after hysterectomy in 39 patients.…”
Section: Voiding Dysfunction Following Routine Hysterectomymentioning
confidence: 98%
“…Since Hanley [33] reported voiding dysfunction as a late complication following hysterectomy there have been many studies that have approached this problem [34][35][36][37][38][39][40][41][42][43][44][45][46][47]. These studies are summarized in Table 46.2.…”
Section: Voiding Dysfunction Following Routine Hysterectomymentioning
confidence: 99%
See 1 more Smart Citation